2019
DOI: 10.1103/physrevb.100.144511
|View full text |Cite
|
Sign up to set email alerts
|

Odd-frequency superconductivity induced by nonmagnetic impurities

Abstract: A growing body of literature suggests that odd-frequency superconducting pair amplitudes can be generated in normal metal-superconductor junctions. The emergence of odd-frequency pairing in these systems is often attributed to the breaking of translation invariance. In this work, we study the pair symmetry of a one-dimensional s-wave superconductor in the presence of a single non-magnetic impurity and demonstrate that translation symmetry breaking is not sufficient for inducing odd-frequency pairing. We consid… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 65 publications
(100 reference statements)
4
14
0
Order By: Relevance
“…For example, if trueĥ describes a generic real‐space tight‐binding Hamiltonian then, if trueΔ̂ is an inhomogeneous on‐site order parameter, then the inequality in Equation is generically satisfied and we expect to find odd‐ω pairing. Note that this is entirely consistent with previous results studying the emergence of odd‐ω pairing in inhomogeneous systems, including at SN interfaces . In contrast, if trueΔ̂ is a spatially homogeneous on‐site order parameter and trueĥ is trivial in spin space and has only real elements, no odd‐ω pairing is possible.…”
Section: General Results For Multiband Odd‐frequency Pairingsupporting
confidence: 91%
See 2 more Smart Citations
“…For example, if trueĥ describes a generic real‐space tight‐binding Hamiltonian then, if trueΔ̂ is an inhomogeneous on‐site order parameter, then the inequality in Equation is generically satisfied and we expect to find odd‐ω pairing. Note that this is entirely consistent with previous results studying the emergence of odd‐ω pairing in inhomogeneous systems, including at SN interfaces . In contrast, if trueΔ̂ is a spatially homogeneous on‐site order parameter and trueĥ is trivial in spin space and has only real elements, no odd‐ω pairing is possible.…”
Section: General Results For Multiband Odd‐frequency Pairingsupporting
confidence: 91%
“…Still, while the existence of such intrinsic odd‐ω order parameters remains an intriguing theoretical question, a great deal of progress has been made studying the emergence of odd‐ω pair correlations in systems with conventional equal‐time order parameters . This latter possibility relies on the conversion of intrinsic even‐ω superconducting correlations to odd‐ω correlations, with a number of proposals in the literature realizing such symmetry conversion through a variety of different mechanisms …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, the authors found that, in general, because tunneling between adjacent layers dominates, an asymmetry emerges between the induced gaps on the two layers. This asymmetry leads directly to odd‐frequency interlayer pairing in such vdW heterostructures, similar to phenomena studied in multiband superconductors, double quantum dots, and double nanowires …”
Section: Superconductor‐based Van Der Waals Systemssupporting
confidence: 57%
“…In this regime Majorana Kramers pairs, or even parafermions if the system is interacting, can be induced. The generation of odd-ω correlations are allowed due to the additional degree of freedom offered by the wire index [116,141]. The authors of Ref.…”
Section: Odd-ω Pairing and Majorana Zero Modesmentioning
confidence: 99%